Analysis of an Interplanetary Coronal Mass Ejection by a Spacecraft Radio Signal: A Case Study. Issue 11 (16th November 2017) - Molera Calvés, G.; Kallio, E.; Cimo, G.; Quick, J.; Duev, D. A.; Bocanegra Bahamón, T.; Nickola, M.; Kharinov, M. A.; Mikhailov, A. G.
Abstract: Tracking radio communication signals from planetary spacecraft with ground‐based telescopes offers the possibility to study the electron density and the interplanetary scintillation of the solar wind. Observations of the telemetry link of planetary spacecraft have been conducted regularly with ground antennae from the European Very Long Baseline Interferometry Network, aiming to study the propagation of radio signals in the solar wind at different solar elongations and distances from the Sun. We have analyzed the Mars Express spacecraft radio signal phase fluctuations while, based on a 3‐D heliosphere plasma simulation, an interplanetary coronal mass ejection (ICME) crossed the radio path during one of our observations on 6 April 2015. Our measurements showed that the phase scintillation indices increased by a factor of 4 during the passage of the ICME. The method presented here confirms that the phase scintillation technique based on spacecraft signals provides information of the properties and propagation of the ICMEs in the heliosphere. Key Points: Detection of a coronal mass ejection by estimation of the phase fluctuations in a spacecraft radio signal Use of VLBI radio telescope to characterize the propagation of spacecraft radio signals along the solar wind